(untitled) (Global Journal of Science Frontier Research, 2017)
The protection of the environment has been at the heart of local communities. The old sages, in most communities creatively fashioned cultural traditions with the goal of conserving the environment while judiciously using its precious resources. It is regrettable that local people and their time-tested cultural practices are neglected in environmental schemes, especially at the consultation and implementation stages. The thrust of the research was to highlight the benefits of incorporating local communities and their cultural traditions in all activities related to the environment using the classic example of the people of Anyinam in Ghana. Focus group discussions and direct observations were the main instrumentations used for soliciting data from the phenomenological study in a qualitative research approach. The study concludes that developmental planners and policy makers must promote the full participation of local communities in environmental schemes to aid in better infrastructure development schemes for the environment.